The Transcendency of José Martí’s Iusphilosophical Thought in the Conception of the Republic for the Peoples of Our America - Bencomo Fariñas, Yeneisi (2020)
José Martí has been called one of the highest exponents of a 19th century philosophical tradition, which continues to this day. His conceptions in the field of law are based on justice, an inherent value to the full dignity of men, center of Marti's axiology and modulator of the unfolding of the rest of the juridical values. This reaches its maximum expression in the republic Martí proposed for Cuba and the other peoples of Latin America. Martí's thought offers us essential guidelines to discover the Latin American identity and autochthony, so crucial to in  facing the challenges and alternatives  for the peoples of Our America today. The article presents an analysis of José Martí's iusphilosophical ideas about the model of republic that he proposes, valid up to the present day, by laying important foundations for its contextualization in the Latin American reality. This work allows us to understand the scope of the Apostle's iuspublistic profile and, especially, its transcendence for Our America, where the search for an authentic model continues to be the key to save the region from the attempts to impose a unique culture in a globalized world.